Pharmacokinetics and skin-tissue penetration of daptomycin in rats - Matsumoto K; Kitaoka M; Kuroda Y; Ikawa K; Morikawa N; Sasaki J; Iketani O; Iwata S; Horino T; Hori S; Kizu J (Dove Medical Press, 2015)
Kazuaki Matsumoto,1 Masashi Kitaoka,1 Yuko Kuroda,1 Kazuro Ikawa,2 Norifumi Morikawa,2 Junichi Sasaki,3 Osamu Iketani,4 Satoshi Iwata,4 Tetsuya Horino,5 Seiji Hori,5 Junko Kizu1 1Division of Practical Pharmacy, Keio University Faculty of Pharmacy, Tokyo, 2Department of Clinical Pharmacotherapy, Hiroshima University, Hiroshima, 3Department of Emergency and Critical Care Medicine, 4Center for Infectious Diseases and Infection Control, Keio University School of Medicine, 5Department of Infectious Diseases and Infection Control, Jikei University School of Medicine, Tokyo, Japan Background: Daptomycin is recommended for complicated skin and skin-structure infections. However, information on the penetration of daptomycin into skin is limited. Therefore, the aim of this in vivo investigation was to determine the pharmacokinetics and skin penetration of daptomycin in rats. Materials and methods: Concentrations of daptomycin were determined by high-performance liquid chromatography. A noncompartmental pharmacokinetic analysis was conducted to estimate the rate and extent of daptomycin penetration from the systemic circulation into skin tissue. Since protein binding of daptomycin in rat serum was 89.3%, the free maximum concentration (Cmax) and free area under the curve from time 0 to infinity (AUC0–∞) for plasma were calculated as follows: fCmax, plasma = (1 – 0.893) × Cmax, plasma, fAUC0–∞, plasma = (1 – 0.893) × AUC0–∞, plasma. Results: The following values (mean ± standard deviation) were obtained: 0.06±0 L/h/kg for total clearance (CLtotal), 0.44±0.06 hours for elimination-rate constant, 1.58±0.23 hours for half-life, 0.14±0.02 L/kg for steady-state volume distribution, and 2.28±0.33 hours for mean residence time. Time to Cmax was 3.0 hours for plasma and skin tissue. Cmax and AUC0–∞ for plasma were 175.8±5.1 µg/mL and 811.8±31.9 µg × h/mL, respectively. Cmax and AUC0–∞ for skin tissue were 19.1±1.7 µg/mL and 113.9±21.8 µg × h/mL, respectively. Furthermore, fCmax and fAUC0–∞ for plasma were 18.8 µg/mL and 86.9 µg × h/mL, respectively. The degrees of skin-tissue penetration, defined as the Cmax, skin tissue/fCmax, plasma ratio and AUC0–∞, skin tissue/fAUC0–∞, plasma ratio, were 1.0 and 1.3, respectively. Conclusion: Daptomycin exhibited good penetration into skin tissue, supporting its use for the treatment of complicated skin and skin-structure infections. However, further studies are needed in infected patients in order to investigate the relationship between the antimicrobial efficacy of daptomycin and its drug concentrations in skin tissues. Keywords: daptomycin, pharmacokinetics, rat, skin-tissue penetration